Penggunaan Metode K-Means dalam Pemetaan Siswa - Yohan Rahman S. Ramli (Neolectura, 2022)
High school (SMA) has several majors and entry requirements for these majors. One of them is senior high school. One of the majors in this high school is the Mathematics and Natural Sciences department, usually there are class groups that are tailored to the knowledge and abilities of prospective students. but there are requirements for prospective new students to be accepted into the Mathematics and Natural Sciences class based on their abilities and knowledge, one of the requirements is the National Examination Score at the Junior High School level, the Mathematics National Examination scores and the Science National Examination scores. The K-Means method is one of the methods used to determine the grouping based on predetermined data